Ruqyah Practice as Islamic Medicine: A Living Qur'an Study - Hudzaifah, Ahmad Faaza (Rumah Moderasi Beragama of Cyber Islamic University Syekh Nurjati Cirebon, 2024)
This research discusses the existence of the practice of retaining the function of the Qur'an beyond its capacity as a revelation, namely